Designing of digital-based Islamic social finance model through role of mosque - Aminah Nuriyah; Ulumuddin Nurul Fakhri (Jurnal Ekonomi & Keuangan Islam, 2022)
Purpose – This study aims to optimize the role of mosques in increasing economic welfare and reducing widespread public usury loans. Moreover, this study also aims to determine the right model for Islamic financial activities.Methodology – This is a qualitative study and the Analytic Network Process (ANP) BOCR model was utilized to obtain the ideal model according to literature reviews and expert opinion. This study conducted in-depth interviews with 5 experts (Ulama, Regulators (Financial Services Authority), Fintech Practitioners, fintech academics, and the Indonesian Mosque Council).Findings – Three alternative models were chosen by the experts, namely the Crowdfunding Model (0.47), Peer-to-Peer landing (0.37), and Bank Infaq (0.17). In addition, the experts suggested for attention to be made to the cost factor (0.47) so as not to burden the mosque. Moreover, according to the experts, the benefits (0.28) that will be obtained will be greater for the welfare of the mosque and residents around the mosque if fintech crowdfunding is implemented.Originality – Research on the role of mosques in improving people's welfare by utilizing fintech is very rarely done. The results of this study are expected to increase the role of the community in collecting funds and controlling the distribution of tabarru' funds.Research limitations – This type of research is exploratory, and empirical research is needed for in-depth results.Practical implications – If this research is implemented, it will accelerate the recovery of economic conditions during a crisis.Social implications – The successful implementation of the Islamic Social Finance (ISF) model by utilizing the role of the mosque will improve the welfare of the community evenly.